Metal-Free Direct C–H Functionalization of Quinoxalin-2(1H)-Ones to Produce 3-Vinylated Quinoxalin-2(1H)-Ones in the Presence of Alkenes - Ding, Rongcai; Li, Yingxue; Chang, Yaoyao; Liu, Yue; Yu, Jie; Lv, Yanna; Hu, Jinxing (Frontiers in Chemistry, 2021)
A novel and efficient C3-H vinylation reaction with quinoxalin-2(1H)-one as the substrate, in the presence of alkenes, under metal-free conditions, is reported herein. The reaction leads to the formation of new carbon–carbon bonds that exhibit moderate to good reactivities. The vinylation of quinoxalin-2(1H)-ones, in the presence of alkenes, is an attractive process that can be potentially utilized to produce biologically active 3-vinylated quinoxalin-2(1H)-ones.